2004
DOI: 10.1002/cncr.20280
|View full text |Cite
|
Sign up to set email alerts
|

The role of craniospinal irradiation in adults with a central nervous system recurrence of leukemia

Abstract: BACKGROUNDAlthough central nervous system (CNS) prophylaxis in patients with leukemia has reduced the incidence of CNS disease recurrence, it still is reported to occur in approximately 5–10% of cases, resulting in a median survival of 6 months. Craniospinal irradiation (CSI) has been shown to improve survival in children who develop a CNS recurrence of acute lymphocytic leukemia (ALL). However, to the authors' knowledge, the role of CSI in adults with a CNS recurrence of leukemia is unknown.METHODSA retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 13 publications
0
29
1
Order By: Relevance
“…Although it has been shown that such an approach is efficient in eradicating the disease from the CNS, the study from Sanders et al failed to show that this was associated with a survival benefit for the patients, mainly because of their very unfavorable prognosis. 12 Unfortunately, successful treatment of CNS-disease did not appear to improve the dismal long-term prognosis of our patients ( Figure 1A). The majority of our refractory patients were treated within the FLAMSA-protocol which is considered to be a reduced intensity conditioning regimen.…”
Section: Resultsmentioning
confidence: 65%
“…Although it has been shown that such an approach is efficient in eradicating the disease from the CNS, the study from Sanders et al failed to show that this was associated with a survival benefit for the patients, mainly because of their very unfavorable prognosis. 12 Unfortunately, successful treatment of CNS-disease did not appear to improve the dismal long-term prognosis of our patients ( Figure 1A). The majority of our refractory patients were treated within the FLAMSA-protocol which is considered to be a reduced intensity conditioning regimen.…”
Section: Resultsmentioning
confidence: 65%
“…Although conventional therapy, such as intrathecal chemotherapy with methotrexate and/or cytarabine, irradiation, and systemic chemotherapy with high-dose cytarabine, are effective, the remission duration is short and relapse rate is high [5][6][7]. Dekker et al [8] reported Biology of Blood and Marrow Transplantation j o u r n a l h o m e p a g e : w w w .…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes for patients with CNSþAML are poor [5,6], and optimal treatment is yet to be established, mainly because of the rarity of this condition. Although conventional therapy, such as intrathecal chemotherapy with methotrexate and/or cytarabine, irradiation, and systemic chemotherapy with high-dose cytarabine, are effective, the remission duration is short and relapse rate is high [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with a CNS recurrence, craniospinal irradiation with or without intrathecal chemotherapy has also been shown to be effective; however, its impact on long-term outcome is unknown. 267 …”
Section: Central Nervous System Involvementmentioning
confidence: 99%